Callous unemotional traits in children with disruptive behavior disorder: Predictors of developmental trajectories and adolescent outcomes. (28th February 2016) - Muratori, Pietro; Lochman, John E.; Manfredi, Azzurra; Milone, Annarita; Nocentini, Annalaura; Pisano, Simone; Masi, Gabriele
Abstract: The present study investigated trajectories of Callous Unemotional (CU) traits in youth with Disruptive Behavior Disorder diagnosis followed-up from childhood to adolescence, to explore possible predictors of these trajectories, and to individuate adolescent clinical outcomes. A sample of 59 Italian referred children with Disruptive Behavior Disorder (53 boys and 6 girls, 21 with Conduct Disorder) was followed up from childhood to adolescence. CU traits were assessed with CU-scale of the Antisocial Process Screening Device-parent report. Latent growth curve models showed that CU traits are likely to decrease linearly from 9 to 15 years old, with a deceleration in adolescence (from 12 to 15). There was substantial individual variability in the rate of change of CU traits over time: patients with a minor decrease of CU symptoms during childhood were at increased risk for severe behavioral problems and substance use into adolescence. Although lower level of socio-economic status and lower level of parenting involvement were associated to elevated levels of CU traits at baseline evaluation, none of the considered clinical and environmental factors predicted the levels of CU traits. The current longitudinal research suggests that adolescent outcomes of Disruptive Behavior Disorder be influenced by CU traits trajectories during childhood. Highlights: We investigated trajectories of CU traits. Latent growth curve showed that CU traits decrease linearly across childhood. Minor decrease of CU traits is associated to poorer adolescence outcomes.